The genus Pedioxestis (Lepidoptera: Oecophoridae) from China, with descriptions of three new species - Wang, Shuxia X. (Zootaxa, 2006)
Four species of Pedioxestis Meyrick, 1932 are recorded from China, including three that are described as new: P. concaviuscula, sp. n., P. bipartita, sp. n., and P. wuyiensis, sp. n. An amended diagnosis of the genus is presented based on the new species. Photographs of the adults and genitalia of the Chinese species are provided, along with a key to the world species.